Nature and Metabolism in Karl Marx’s Capital - Quesada Rodríguez, Francisco (2025)
This research discusses the concept of Nature and Metabolism in Karl Marx’s Capital I, taking as a background the time-worn Marxist interpretations regarding the relationship of human beings with nature and new discussions about the ecological character of Marx’s philosophy. During the second half of the twentieth century, human relationships with nature were considered within the framework of alienation through work to the extent that nature appears as the object of a constant struggle for private appropriation for production, dissociating “Man” and Nature. However, in relation to the current environmental discussions in the 21st century, a new organic dimension has been discovered that had been forgotten in Marxist philosophy: Metabolism. Finally, from the perspective of Nature and Metabolism, Marx’s contribution to the ecological question against capitalism is critically discussed, considering the so-called “metabolic rift”